Determinants of carbon finance uptake and its role in deployment of renewable energy projects in Kenya - Baimwera, Bernard (Strathmore University, 2018)
Carbon finance has been advanced as a strong financial mechanism to help the world transition to low carbon development, in the face of ravaging climate change. Projects that sequester greenhouse gases from the atmosphere are eligible to accrue carbon finance, either through sale of carbon credits in the designated carbon markets or through other flexible mechanisms. This thesis analyzed the determinants of carbon finance accrual in renewable energy projects, in the context of a low and middle income country, Kenya. The aim was to explore the role played by carbon finance in promoting the deployment of renewable energy, as envisaged in the international climate agreements, for a country with a reportedly enormous renewable energy potential. While carbon finance use in renewable energy has been extensively analyzed in developed countries, low and middle income countries, especially those in Africa, have received considerably less attention. In an attempt to address this gap, the thesis analyzed the determinants of carbon finance uptake in renewable energy projects registered under the Feed-in-Tariff scheme of the Kenyan government. Renewable energy projects were selected because prior evidence shows that a significant percentage of carbon finance is targeted to these projects, because of their emission reducing abilities. Triangulation of methodology, including the use of questionnaires, interviews and analysis of policy documents, was used to collect and analyze qualitative and quantitative data from renewable energy projects and other carbon business stakeholders on their understanding, uptake and determinants of carbon finance accrual in renewable energy projects. In addition to analyzing the determinants of carbon finance uptake, the study uncovered the constraints of accessing carbon finance and the challenges renewable energy developers face in the country. The evidence and analyses presented reveal that the size of the renewable energy project, the carbon market affiliation of the project and the level of low carbon technology employed in the project are significant determinants of carbon finance flows into the projects. At the same time, lack of capital to develop renewable projects to completion, primarily the absence of financial instruments from local banks and high transaction costs to meet carbon credits generation were identified as the main constraints in accessing carbon finance by the developers. The analyses also reveal low levels of understanding and awareness of the carbon finance uptake, suggestive of the low levels of uptake that were uncovered by the study. Based on these findings, the research recommends for the creation of a framework to educate and create awareness to local renewable energy developers on the existence and processes of accessing carbon funds from international carbon markets. There is also need to develop financial instruments to cater for risk investments with environmental benefits like those in renewable energy in the Kenyan capital market.
A Research Thesis submitted in total fulfilment of the requirements for the award of the Degree of Doctor of Philosophy in Finance at Strathmore University
Keywords: Carbon Finance; Renewable Energy Projects; Low Carbon Development; Greenhouse Gases